Trametes versicolor: Potential for atrazine bioremediation in calcareous clay soil, under low water availability conditions. - Bastos, Ana Catarina; Magan, Naresh (Elsevier, 2009)
This study examined the feasibility of Trametes versicolor to actively degrade atrazine (0.5 μg g−1) in non-sterile calcareous clay soil (Algarve, Portugal) microcosms for up to 24 weeks (20 °C), under low water availability (soil water potentials of −0.7 and −2.8 MPa). Soil respiration, laccase activity, and atrazine quantification by high-performance liquid chromatography (HPLC) were assessed. Respiration was significantly (p < 0.05) enhanced in soil containing the inoculant, particularly in the presence of atrazine, indicating that it remained metabolically active throughout the study. Furthermore, up to 98% and 85% (at −0.7 and −2.8 MPa, respectively) of atrazine was degraded in soil containing both the atrazine and the inoculant, compared to 96% and 50% in soil containing atrazine only. The contribution of T. versicolor to atrazine degradation was only significant (p < 0.005) under the driest soil treatment conditions. The strategies used for enhancing colonisation and biodegradation capabilities of the inoculant, as well as the selection of sawdust as carrier, were thus effective. However, there were no differences (p > 0.05) in quantified laccase activity in soil containing the inoculant and the control. Overall, this study demonstrated that T. versicolor was a strong candidate for atrazine bioremediation in soil with low moisture and organic matter contents, such as that found in semi-arid and Mediterranean-like ecosystems.
Keywords: Trametes versicolor; Biodegradation; Atrazine; Soil microcosms; Water potential; Soil respiration; Laccase activity